In vivo anti-inflammatory properties of aerial parts of Nasturtium officinale. (February 2014) - Sadeghi, Heibatollah; Mostafazadeh, Mostafa; Sadeghi, Hossein; Naderian, Moslem; Barmak, Mehrzad Jafari; Talebianpoor, Mohammad Sharif; Mehraban, Fouad
Abstract Context: Nasturtium officinale R. Br. (watercress) has long been used in Iranian folk medicine to treat hypertension, hyperglycemia, and renal colic. Moreover, anticancer, antioxidant, and hepatoprotective properties of N. officinale have been reported. Objective: In this study, anti-inflammatory activity of the hydro-alcoholic extract from aerial parts of N. officinale was investigated. Materials and methods: Oral administration of the hydro-alcoholic extract of N. officinale (250, 500 and 750 mg kg−1) was investigated on two well-characterized animal models of inflammation, including carrageenan- or formalin-induced paw edema in rats. Then, the topical anti-inflammatory effect of N. officinale (2 and 5 mg/ear) was studied on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced mouse ear edema. Finally, biopsy of the paw or ear was performed for pathological evaluation. Results: Acute toxicity tests of N. officinale in rats established an oral LD50 of >5 g kg−1. The extract of watercress (250, 500 and 750 mg kg−1) significantly inhibited carrageenan-induced paw edema 1, 2, 3 and 4 h after carrageenan challenge (p < 0.001). The extract (500 mg kg−1) also showed considerable activity against formalin-evoked paw edema over a period of 24 h (p < 0.001). Furthermore, topical application of N. officinale (5 mg/ear) reduced TPA-induced ear edema (p < 0.05). Histopathologically, the extract decreased swelling and the tissue damage induced by carrageenan or TPA. Discussion and conclusion: Our findings indicate potent anti-inflammatory activity of N. officinale in systemic and topical application and propose its potential as an anti-inflammatory agent for treatment of inflammatory conditions.